2000
DOI: 10.1016/s0735-1097(00)00548-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic demonstration of manipulation-related aortic injuries after cardiac surgery

Abstract: This study demonstrated an association between new lesions created by surgical maneuvers and postoperative stroke. Embolic strokes were more likely to occur if new lesions were complicated with intimal disruption, especially of the mobile type. Modifications in surgical procedures will be needed if thick plaque (especially >4 mm) is noted near the manipulation site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 13 publications
1
37
0
Order By: Relevance
“…Ura and colleagues demonstrated that stroke might be caused not only by aortic clamping but by jet from the arterial cannula. 4 Based on rheological and pathological observation, orifi ces of arch vessels tend to have dense deposition of atheromatous plaque, which is observed as paste-like material spilling out from the arterial wall during surgery. 20 Sometimes patients have mobile, fragile plaque around the ostium of the BCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ura and colleagues demonstrated that stroke might be caused not only by aortic clamping but by jet from the arterial cannula. 4 Based on rheological and pathological observation, orifi ces of arch vessels tend to have dense deposition of atheromatous plaque, which is observed as paste-like material spilling out from the arterial wall during surgery. 20 Sometimes patients have mobile, fragile plaque around the ostium of the BCA.…”
Section: Discussionmentioning
confidence: 99%
“…3 In these conditions, manipulation of the ascending aorta, including cannulation and clamping, may cause deleterious atheroembolism and should be avoided. 4,5 Retrograde perfusion from the femoral artery may induce paradoxical atheroembolism to the brain in patients with iliac artery atherosclerosis, an abdominal aortic aneurysm, and/or a descending aortic aneurysm. Although axillary artery perfusion is one of the solutions for this problem, there are several limitations to this method.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluation for atherosclerosis of the aorta is not routinely performed preoperatively in children, although atheroembolism from the ascending aorta is a major etiologic factor for stroke in adult patients undergoing cardiac surgery. Cohen et al (6) showed that non calcified plaques are associated with a higher risk of vascular events and surgical manipulation has been reported to cause new mobile lesions in a diseased aorta (7). Soft atheromas are most likely to embolized as a result of manipulation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have identified patientspecific risk factors for stroke associated with CABG as follows: prior stroke or transient ischemic attack [2,13,14], carotid artery stenosis [15][16][17][18], aortic atherosclerosis [19,20], atrial fibrillation [3,21], peripheral arterial disease [21], prior cardiac surgery [22], poor baseline clinical condition [3,23], left ventricular dysfunction [21], prolonged time on cardiopulmonary bypass (CPB) [21,22], conventional onpump CABG [22] and older age [2,3]. The presence of any one risk factor for stroke is not considered a contraindication [13].…”
Section: Risk Factorsmentioning
confidence: 99%